The motives using google classroom as a distance learning media during the covid-19 pandemic at the elementary school level in pontianak - Suparjan Suparjan; Mariyadi Mariyadi (Premiere Educandum : Jurnal Pendidikan Dasar dan Pembelajaran, 2021)
The spread of the COVID-19 pandemic in Indonesia since the early March 2020 has change most sectors of human’s life together with  educational activities. Many schools tried to adapt to conduct instructional activities from the distance and students’ learning activities were implemented from home via online. Teachers and students were expected to be able to use online learning flatforms and media to support their activites for the sake of avoiding the spread of the virus. This study aims to investigate the teachers’ motives for using Google Classroom as a media for distance learning during the COVID-19 pandemic at the Elementary School Level. This research applied a qualitative descriptive study and   semi-structured interviews was utilized to collect data from eight respondents of three elementary schools who are actively using Google Classroom in teaching and learning activities in Pontianak City. The findings indicate that  there are 5 motives for using Google Classroom during the COVID-19 pandemic at elementary schools in Pontianak City which cover  ease of  access and use,  application shopistiation, availability of  facilities and infrastructure, school policy, and  level of teacher and students' digital literacy skills.